International Model for Policy Analysis of Agricultural Commodities and Trade–Standard IFPRI Multimarket Model (IMPACT-SIMM) - CGIAR Research Program on Policies, Institutions, and Markets (2021)
The documentation of IMPACT-SIMM was published in a 2021 Discussion Paper.